Prevalence and complication of COVID‐19 in patients with ankylosing spondylitis (AS) and its relationship with TNF‐a inhibitors - Shafieh Movassaghi; SeyedAhmad SeyedAlinaghi; Abdolrahman Rostamian; Seyed Reza Najafizadeh; Elham Nezhadseifi (Immunity, Inflammation and Disease)
Abstract Introduction Ankylosing spondylitis (AS) is a condition that is treated with nonsteroidal anti‐inflammatory drugs and biological drugs such as anti tumor necrosis factor alpha (TNF‐α). This study examined the prevalence of COVID‐19 among individuals with AS and compare it between those receiving and not receiving TNF‐α inhibitors. Methods A cross‐sectional study was conducted at the rheumatology clinic of Imam Khomeini Hospital in Tehran, Iran. The study included patients with AS who sought treatment at the clinic. Demographic information, laboratory and radiographic findings, and disease activity were recorded through interviews and examinations using a questionnaire. Results A total of 40 patients were studied over the course of 1 year. Among them, 31 patients were administered anti‐TNF‐α drugs, with 15 patients (48.3%) receiving subcutaneous Altebrel (Etanercept), 3 patients (9.6%) receiving intravenous Infliximab, and 13 patients (41.9%) receiving subcutaneous Cinnora (Adalimumab). Of the total, 7 patients (17.5%) tested positive for COVID‐19, 1 of whom was confirmed through both CT scan and polymerase chain reaction (PCR) testing, while the remaining 6 patients were confirmed only through PCR testing. All patients tested positive for COVID‐19 were male, and 6 of them had received Altebrel. Among the 9 AS patients who did not receive TNF inhibitors, 1 patient contracted SARS‐CoV‐2. The clinical symptoms experienced by these patients were mild, and hospitalization was not required. However, 1 patient who had insulin‐dependent type 1 diabetes and was receiving Infliximab required hospitalization. This patient exhibited more severe COVID‐19 symptoms, including high fever, pulmonary involvement, dyspnea, and decreased oxygen saturation. No cases of COVID‐19 were reported in the Cinnora treatment group. The use of any of the drugs did not demonstrate a significant relationship with the occurrence of COVID‐19 in patients. Conclusions The use of the TNF‐α inhibitors in patients with AS, may be associated with reduced hospitalization and death rate in COVID‐19 cases.